PERCEPTION OF STUDENTS ON THE DEGREE COURSE IN GEOGRAPHY AT UNIMONTES IN RELATION TO THE USE OF DIGITAL TECHNOLOGY IN EDUCATION - Rodrigues Rocha, VanessaTamiris; Fernandes dos Santos, Maria Ines; de Carvalho Alves, Rahyan (Revista Contexto Geográfico, 2025)
The objective of this work is to briefly highlight the perception of students of the 6th term of the degree course in Geography, at the university located in the north of Minas Gerais about the use of digital technology in education. For that, the quantitative and qualitative method was used and as methodology: bibliographic review and analysis of data collected in work/field exercise carried out in April 2023, with the application of questionnaires to students. It is considered that most of the interviewees have already made use of technological resources in their classroom experiences. And, in a majority way, they see this use as beneficial for students’ learning, since it tends to contribute to the improvement of this process, stimulating creativity and making teaching more attractive.